2017
DOI: 10.1083/jcb.201607096
|View full text |Cite
|
Sign up to set email alerts
|

Congressing kinetochores progressively load Ska complexes to prevent force-dependent detachment

Abstract: Auckland et al. describe a previously overlooked step during chromosome congression that provides insight into how kinetochore maturation is linked to attachment load-bearing, microtubule occupancy, and spindle assembly checkpoint signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 48 publications
4
58
0
Order By: Relevance
“…Again, these results support that Thr358 and Thr360 are the major sites contributing to Ska functions. Of note, our results also suggest that the Ska complex may be dispensable for chromosome congression to metaphase plates from initial attachments (Figures S4A and S4B), consistent with the previous findings (Auckland et al, 2017;Daum et al, 2009). The significant delay in our experiments was derived from metaphase-to-anaphase transition.…”
Section: Cdk1 Phosphorylation On the Six Sites In Ska3 Is Required Fosupporting
confidence: 92%
See 2 more Smart Citations
“…Again, these results support that Thr358 and Thr360 are the major sites contributing to Ska functions. Of note, our results also suggest that the Ska complex may be dispensable for chromosome congression to metaphase plates from initial attachments (Figures S4A and S4B), consistent with the previous findings (Auckland et al, 2017;Daum et al, 2009). The significant delay in our experiments was derived from metaphase-to-anaphase transition.…”
Section: Cdk1 Phosphorylation On the Six Sites In Ska3 Is Required Fosupporting
confidence: 92%
“…However, how this is achieved is not fully understood. In cells, Ska starts to accumulate at kinetochores in prometaphase and peaks at metaphase (Auckland et al, 2017;Hanisch et al, 2006). The dynamic localization pattern coordinates well with the process of establishing proper kinetochoremicrotubule interactions from prophase to metaphase, suggesting that Ska binding to kinetochores could be important for its functions.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In contrast, both MTBD-microtubule interactions support force generation, which suggests that kinetochores utilise diffusion-based and curved-protofilament coupled mechanisms to produce tension. It is well established that the latter is mediated by the Ska complex (Schmidt et al, 2012), which is crucial for providing load-bearing capability to kinetochores in vivo (Auckland et al, 2017) and in vitro (Helgeson et al, 2018). However, the CENP-F MTBDs do not appear to contribute as they are dispensable for chromosome congression.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the Ska complex is important for establishing and/or maintaining end‐on kinetochore‐microtubule attachments. Recently, detailed analysis of kinetochore attachments using live imaging demonstrated that the Ska complex functions to prevent force‐dependent detachment of kinetochores from microtubules in the process of chromosome congression, which helps to stabilize the end‐on kinetochore attachments and promote proper chromosome alignment …”
Section: Ska Promotes End‐on Kinetochore Attachmentsmentioning
confidence: 99%